The effects of continuous vs intermittent oxygen supplementation on repeat sprint cycling performance - Porter, M. S.; Reed, K. (Journal of Human Sport & Exercise, 2022)
The use of handheld cannisters providing supplementary oxygen to use `track side` is becoming popular. The aim of this study was to determine the optimal time to administer oxygen supplementation (O2Supp) during a repeat sprint protocol on cycling performance. Ten male recreationally active University students participated. Testing comprised four visits to the laboratory in a counterbalanced design. Each session entailed ten x 15s repeated sprints interspersed with 45s passive recovery, during which the air inspired was either 100% oxygen (H) or normal air, (N), thus the oxygen content inspired during the sprints and/or the recovery periods, determined the four conditions; NH, HN, HH, NN respectively. It was hypothesised that the HH condition would evoke the largest performance improvements. Repeated measures ANOVA were used to examine the difference between conditions in the outcome measures of mean power (W), rate of power decline (%) and blood lactate (mmol/L). There was no significant effect of O2Supp on mean power (W), blood lactate or performance decline (%) (p > .05), although. the HH condition did result in the lowest levels of lactate accumulation and the shallowest decline in performance. The NH and HN conditions resulted a greater decline in performance than both HH and NN. Continuous O2Supp during repeat sprint cycling is more effective on cycling performance, than when it is administered in short repeated bouts. It appears that the rapid changing of oxygen availability may have a detrimental effect on performance. O2Supp can be applied to training programmes that have extended (>1min) periods of recovery.